The International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT): Model documentation for version 3.6 - Robinson, Sherman; Dunston, Shahnila; Mishra, Abhijeet; Sulser, Timothy B.; Mason-D’Croz, Daniel; Robertson, Richard D.; Cenacchi, Nicola; Thomas, Timothy S.; Zhu, Tingju; Gueneau, Arthur; Pitois, Gauthier; Wiebe, Keith D.; et al. (International Food Policy Research Institute, 2024)
The International Food Policy Research Institute’s IMPACT model is a robust tool for analyzing global and regional challenges in food, agriculture, and natural resources. Continuously updated and refined, IMPACT version 3.6 is the latest update to the model for continuously improving the treatment of complex issues, including climate change, food security, and economic development. IMPACT 3.6 multimarket model integrates climate, crop simulation, and water models into a comprehensive system, providing decision-makers with a flexible platform to assess the potential impacts of various scenarios on biophysical systems, socioeconomic trends, technologies, and policies.